(untitled) (Agricultural Engineering, 2019)
The article presents an algorithm for calculating selected energy assessment indexes for grain driers. Particular attention was paid to the conversion of the equations obtained for the operating conditions of the drying process into equations allowing the calculation of indexes for the standard drying conditions. The indexes obtained allow a proper comparison of dryers operating in varied atmospheric conditions, as well as humidity and temperature of the dried material.